MARKETING DEVELOPMENT STRATEGY OF BETT FISH (Betta sp.) IN MEDAN CITY - Mhd Hafizur Rasyid Siregar (Institute of Computer Science (IOCS), 2020)
In this study, the population is the betta fish business actors in Medan City. While the sample is 20 respondents. The analysis of this study was carried out using qualitative data, with a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The results of this study indicate the position of the betta fish marketing development strategy in Medan City is in quadrant III, which means the position of the betta fish marketing development strategy is in the turn around strategy position where this strategy shows a large enough opportunity but on the other hand it still has several internal weaknesses.